R-curve behavior and crack propagation properties of asphalt concrete at low temperatures - Ghafari, Sepehr; Moghadas Nejad, Fereidoon (Journal of Civil Engineering and Management, 2015)
Fracture properties and crack propagation characteristics of asphalt concrete mixtures were studied by obtaining fracture resistance curves using three point single edge SE(B) notched beam specimens. Elastic-plastic approach is used in the calculation of the J-integral since the fracture process zone size is large enough to not use a linear elastic approach. Crack length measurements were obtained directly from high resolution images taken during the tests. A rising R-curve was observed in all the specimens which indicates ductility and a toughening mechanism in the ductile to quasi-brittle fracture of the mixture. Mixtures developed by limestone and siliceous aggregates with 4%, 4.5% and 5% binder contents were tested at temperatures ranging from +5ºC to –20ºC. Mixtures with 5% binder content showed greater crack resistant behavior at each temperature. Crack lengths at which crack propagation instability occurred were decreased by the reduction of temperature. A significant drop of this critical crack length is observed in temperatures below –15ºC. As well, the elastic-plastic fracture toughness is increased by the reduction of temperature up to –15ºC and starts to diminish thereafter.